Analysis of The Implementation System of The Children's Diarrhea Cross Program at The Andalas Community Health Center in Padang City - Halimah, Siti; Gusti, Aria; Masrizal, Masrizal; Syafrawati, Syafrawati; Ayulia, Ayulia (JIK-JURNAL ILMU KESEHATAN, 2026)
The LINTAS Diarrhea program for toddlers was carried out by the Andalas Health Center but only achieved 76% of its target in 2022. This research aimed to evaluate how the program was implemented at the health center in 2023. A descriptive qualitative approach was applied, involving nine informants chosen through purposive sampling. The study took place from November to July 2024. Data collection methods included in-depth interviews, field observations, and document analysis. Data were then processed through reduction, display, and conclusion drawing, and validated using source and method triangulation. Although the program referred to the Indonesian Minister of Health Regulation No. 1216 of 2001, not all staff were aware of the policy. Staff members often faced multiple roles and heavy workloads. Funding and infrastructure remained inadequate. Furthermore, setting of program targets and delivery of preventive education had not been optimal. The program was not fully aligned with the LINTAS Diarrhea Program Pocket Book, and delays occurred in recording and reporting activities. Although monitoring and evaluation were carried out, overall program execution was still lacking. Therefore, improvements are needed, including better funding, additional personnel, improved facilities, and stricter adherence to program guidelines for optimal diarrhea prevention in toddlers.